Dual‐Isotope Constraints on Seasonally Resolved Source Fingerprinting of Black Carbon Aerosols in Sites of the Four Emission Hot Spot Regions of China. Issue 20 (21st October 2018) - Fang, Wenzheng; Du, Ke; Andersson, August; Xing, Zhenyu; Cho, Chaeyoon; Kim, Sang‐Woo; Deng, Junjun; Gustafsson, Örjan
Abstract: Despite much recent efforts, the emission sources of black carbon (BC) aerosols―central input to understanding and predicting environmental and climate impact―remain highly uncertain. Here we present observational δ 13 C/Δ 14 C‐based constraints on the sources of BC aerosols over the four seasons in each of the four key hot spot emission regions of China: Beijing‐Tianjin‐Hebei (BTH‐Wuqing; where Wuqing is the sampling location), Yangtze River Delta (YRD‐Haining), Pearl River Delta (PRD‐Zhongshan), and Sichuan Basin (SC‐Deyang). Overall, BC loadings were highest in winter, yet elevated loadings were also observed in other seasons, for example, spring at SC‐Deyang and fall at PRD‐Zhongshan. Annually, the dominant BC sources were coal (50 ± 20%) for BTH‐Wuqing, liquid fossil for YRD‐Haining (46 ± 8%) and PRD‐Zhongshan (48 ± 18%), whereas liquid fossil (42 ± 17%) and biomass burning (41 ± 14%) equally affected SC‐Deyang. There is also different but distinct seasonalities in BC sources for the different sites. As an example, for BTH‐Wuqing coal burning increased from summer to winter, while summer and spring BTH‐Wuqing were more influenced by liquid fossil. In contrast, for YRD‐Haining, the relative importance of emission sources was more constant over the year. These quantitative observational constraints on source‐seasonality of BC aerosols in receptor sites located in China's four key economic zones highlight that regulatory control on BC aerosol emissions from different fuels should consider both seasonal and regional variations. Our results also suggest that models on estimates of BC‐induced climate and air quality should consider variations over both regional and seasonal scales. Key Points: Our observation‐based results show a strong source seasonality of black carbon aerosol for BTH, PRD, and SC, while little variation for YRD Annually, the dominant BC sources are coal for BTH, liquid fossil for YRD and PRD, whereas SC is dominated by biomass and liquid fossil fuels Our results suggest that regionally seasonally tailored mitigation strategies are crucial to effectively reducing aerosol pollution in China